EAP authentication mechanism for Ad Hoc wireless LAN - M. Agni Catur Bhakti,; Azween Abdullah,; Low, Tan Jung; Halabi Hasbullah, (Penerbit UKM, 2008)
Wireless networks have some security issues, mainly due to its wireless nature (open and non-physical), that need to be addressed. One of the solutions to improve wireless network security is the IEEE 802.1X specification, which is based on Extensible Authentication Protocol (EAP). EAP is an authentication framework that can support multiple authentication methods. With its advantage of being flexible, EAP has been used in many types of networks, wired and wireless, including the infrastructure model of wireless LAN. With EAP’s flexibility, it might be also possible to use EAP as a generic authentication mechanism in other types of networks. This paper studies and explores the feasibility of using EAP in ad-hoc model of WLAN and proposes a mechanism to implement EAP in ad hoc WLAN based on EAP multiplexing model. We also propose a mechanism to select a suitable EAP method out of a set of EAP methods to be used in authentication process in heterogeneous wireless network, in which there are different types of nodes with different specifications and capabilities in the network. Thus, each node may support a different type of EAP authentication method. Toward the end of this paper, we formally specify and verify the proposed authentication mechanism in order to proof and obtain strong beliefs of the authentication.